2007
DOI: 10.1080/07357900701208808
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Thalidomide Alone versus Thalidomide Plus Interferon Alpha in Patients with Refractory Multiple Myeloma

Abstract: The potential synergistic anti-myeloma effect for thalidomide combining with interferon alpha was not yet clear clinically. From March 2001 to January 2004, a total of 28 heavily pretreated multiple myleoma (MM) patients were enrolled in this open-labeled, randomized Phase II study. Patients with refractory MM were randomized to receive either thalidomide alone (200 mg/day up to the maximum dose 800 mg/day, arm B) or the combination of thalidomide and interferon alpha (3 MIU/m(2) subcutaneous injection 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is in wide use to treat chronic myelogenous leukemia, CML, 2,3 melanoma, 4,5 myeloma 6,7 and renal cell carcinoma, RCC. 8,9 IFNa is actually a family of a dozen related, approximately 166 amino acid, 16 to 20 kDa proteins.…”
Section: Ifnamentioning
confidence: 99%
“…It is in wide use to treat chronic myelogenous leukemia, CML, 2,3 melanoma, 4,5 myeloma 6,7 and renal cell carcinoma, RCC. 8,9 IFNa is actually a family of a dozen related, approximately 166 amino acid, 16 to 20 kDa proteins.…”
Section: Ifnamentioning
confidence: 99%
“…Thus, we suggest that IFN-α is not different than any of these new novel drugs and that expanded combination maintenance therapy, including GM-CSF and IFN-α, should be further investigated. Few studies have been published on combining interferon or peginterferon with thalidomide, [54][55][56] which showed high rate of adverse effects and intolerance to the combination. Another study reported the use of combination of 13 cis-retinoic acid, dexamethasone and IFN-α as maintenance for MM patients post ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…The response time is less than thalidomide alone, the duration of the response is greater and the EFS is better despite the OS being similar between the two treatments. The most frequent adverse events in the two forms of treatment are neutropenia, anemia, thrombocytopenia, constipation, drowsiness and skin rash, but grade 3 and 4hematologic toxicity is higher with the use of thalidomide ( 72 ) (A).…”
Section: What Are the Best Treatment Options For Relapsed MM Patients?mentioning
confidence: 99%